IMPLEMENTASI METODE TALQIN DALAM PEMBELAJARAN AL-QUR'AN (Studi Kasus di TPQ Masjid Abu Bakar, KOTA BENGKULU) - Aprilia Pratiwi, Chantika; Chandra, Pasmah; Novita, Atia; Orenti, Selvi; Rahmadania (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of the Talqin method in Quranic learning at the Taman Pendidikan Al-Qur'an (TPQ) of Masjid Abu Bakar, Bengkulu City. The Talqin method is a direct oral transmission approach (talaqqi musyafahah) recognized as the most authentic method in the Islamic scholarly tradition, yet it remains understudied in the context of non-formal TPQ institutions. This study employs a descriptive-analytical qualitative approach, with data collected through participatory observation, in-depth interviews, documentation study, and Focus Group Discussion (FGD), conducted during the Community Service Program (Kuliah Kerja Nyata/KKN) of Group 11 in May–June 2026. The findings indicate that: (1) instructional planning has been systematically structured through a four-tiered curriculum; (2) implementation proceeds through three structured phases, with musyafahah and sorogan interactions as the core; (3) the evaluation system encompasses four competency aspects (fluency, makhraj, tajwid, and memorization); and (4) this method has been shown to improve Quranic reading ability by an average of 28–42% within one year. The primary challenges identified are a non-ideal teacher-to-student ratio and heterogeneity in students' ability levels. This study concludes that the Talqin method remains relevant and superior in the context of modern Quranic education, with recommendations for development in the areas of teaching resource management and digitalization of record-keeping systems